The early positivists' approach to scientific discovery - Meheus, Joke (Philosophica, 1999)
In the early eighties, philosophers of science came to the conviction that discovery and creativity form an integral part of scientific rationality. Ever since, the "positivists" (logical positivists and their immediate forerunners) have been criticised for their (alleged) neglect of these topics. It is the aim of this paper to show that the positivists' approach to scientific discovery is not only much richer than is commonly recognized, but that they even defended an important thesis which some of the 'friends of discovery' seem to have forgotten. Contrary to what is generally accepted, I shall also show that there is no reason at all why the positivists should have ignored discovery.